Kisspeptins and the neuroendocrine control of reproduction: Recent progress and new frontiers in kisspeptin research - Sobrino Veronica; Avendano Maria Soledad; Perdices-Lopez Cecilia; Jimenez-Puyer Manuel; Tena-Sempere Manuel (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2026)
In late 2003, a major breakthrough in our understanding of the mechanisms that govern reproduction occurred with the identification of the reproductive roles of kisspeptins, encoded by the Kiss1 gene, and their receptor, Gpr54 (aka, Kiss1R). The discovery of this unsuspected reproductive facet attracted an extraordinary interest and boosted an intense research activity, in human and model species, that, in a relatively short period, established a series of basic concepts on the physiological roles of kisspeptins. Such fundamental knowledge, gathered in these early years of kisspeptin research, set the scene for the more recent in-depth dissection of the intimacies of the neuronal networks involving Kiss1 neurons, their precise mechanisms of regulation and the molecular underpinnings of the function of kisspeptins as pivotal regulators of all key aspects of reproductive function, from puberty onset to pulsatile gonadotropin secretion and the metabolic control of fertility. While no clear temporal boundaries between these two periods can be defined, in this review we will summarize the most prominent advances in kisspeptin research occurred in the last ten years, as a means to provide an up-dated view of the state of the art and potential paths of future progress in this dynamic, and ever growing domain of Neuroendocrinology.